Adaptive Cruise Control Strategies Implemented on Experimental Vehicles: A Review. Issue 5 (2019) - He, Yinglong; Ciuffo, Biagio; Zhou, Quan; Makridis, Michail; Mattas, Konstantinos; Li, Ji; Li, Ziyang; Yan, Fuwu; Xu, Hongming
Abstract: It has been over two decades since the first generation of adaptive cruise control (ACC) equipped vehicles were launched onto the market. However, control strategies adopted by commercially available ACC systems are the closely-guarded intellectual property of their industrial developers, so these are not publicly available and there is no uniform standard for ACC dynamic response. However, the impact of ACC dynamics on transport networks needs to be studied. In the open literature, there are many ACC systems published and embedded in simulation studies, nevertheless, inappropriate model design can easily point to misleading conclusions. Only a few projects dealing with automated systems are founded on real experimental data, which is important for developing precise ACC models and furthermore, evaluating their realistic effects on highway capacity and traffic flow dynamics. This review firstly summarizes the available literature on control strategies for ACC systems implemented on experimental vehicles, then propose a five-layer framework for the development and evaluation of ACC or CACC control strategies based on future trends.